Mitigating greenhouse gas emissions in Kenya's food system: Economic interdependencies and policy opportunities - Nin-Pratt, Alejandro (International Food Policy Research Institute, 2023)
Low- and middle-income countries worldwide share the common challenge of achieving sustainable economic development while reducing greenhouse gas (GHG) emissions. This challenge is complex due to the interconnectedness of economic activities, where policies targeting one industry can have ripple effects on others. Therefore, it is crucial to understand integrated GHG emissions and their relationships across industries within an economy to inform effective policy formulation. Kenya, as a middle-income country experiencing rapid economic growth, faces an urgent need to address this challenge. This study analyzes the economic relationships between agricultural production, the food industry, and other sectors of the economy in Kenya to identify key drivers of national GHG emissions from the food system. To accomplish this, an environmentally extended input-output (EEIO) table is employed to calculate both direct and indirect emissions for 38 activities of Kenya’s economy, as well as emissions embodied in final goods. Direct emissions refer to those generated during the production process of an activity, while indirect emissions are produced by other activities that provide inputs to the activity of interest. The findings reveal that agriculture is the largest contributor to GHG emissions in Kenya, with the majority of emissions stemming from direct sources such as enteric fermentation and manure management in livestock production. Additionally, the study finds that total emission intensity in the manufacturing sector is considerably higher than in most agricultural activities, except for livestock production, primarily due to the significant level of indirect emissions associated with manufacturing processes. Within the agricultural sector, cereals and livestock production exhibit high levels of direct emissions, while export crops like coffee and tea, as well as vegetable cultivation, show relatively higher indirect emissions. Addressing GHG emissions from the livestock sector emerges as a crucial step in significantly reducing agricultural emissions in Kenya. The dairy sub-sector presents an opportunity for intensification and technological advancements, as climate-smart technologies have already demonstrated their potential to enhance productivity while reducing emissions. Conversely, mitigating GHG emissions in beef production, which is primarily concentrated in ecologically fragile areas, will require institutional innovations focusing on rangeland management, disease control, and scaling up livestock marketing efforts. While the intensification of dairy production can contribute to agricultural growth and development in Kenya, its impact on mitigating GHG emissions is expected to be limited at the national scale.